2021
DOI: 10.3389/fcell.2021.651560
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4 as a Favorable Prognostic Marker in Bladder Cancer: A Multi-Omics Analysis

Abstract: BackgroundThe toll-like receptor 4 (TLR4) agonist, Bacille Calmette-Guérin, has exhibited gratifying effects in treating bladder cancer. The study aims to explore the expression pattern, prognostic value, and potential mechanism of TLR4 in bladder cancer.MethodsThe transcriptome file from the GSE13507 dataset in the Gene Expression Omnibus database and the promoter methylation file from the bladder cancer dataset in The Cancer Genome Atlas database were downloaded for analysis. The prognostic value of the TLRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
(28 reference statements)
1
10
0
Order By: Relevance
“…For example, CALR was more highly-expressed in BCA patients than controls, meanwhile survival analysis showed CALR was a risk factor. So far, the role of TLR4 in BCA has been extensively explored ( Lu et al, 2021 ), consistent with our results showing TLR4 was a protective factor. However, the correlation between BCA and CALR has been rarely reported.…”
Section: Discussionsupporting
confidence: 92%
“…For example, CALR was more highly-expressed in BCA patients than controls, meanwhile survival analysis showed CALR was a risk factor. So far, the role of TLR4 in BCA has been extensively explored ( Lu et al, 2021 ), consistent with our results showing TLR4 was a protective factor. However, the correlation between BCA and CALR has been rarely reported.…”
Section: Discussionsupporting
confidence: 92%
“…TLR4 expression can effectively predict oncological outcomes and drug sensitivity of BLCA patients. TLR4 was also associated with infiltrating immune cell variation and cancer pathway dysregulation [ 28 ]. In another study, researchers found that TLR4 may contribute to immune escape of UBC.…”
Section: Discussionmentioning
confidence: 99%
“…The half inhibitory concentration (IC50) of chemotherapeutic and targeted therapeutic drugs in different risk groups were calculated by the “pRRophetic” R package 33 , 34 , then we predicted the drugs sensitivity between two risk groups to chemotherapy 35 37 . Immunophenoscore (IPS) of the TCGA-GC cohort was downloaded from The Cancer Immunome Atlas (TCIA; https://tcia.at/home ; Table S2 ).…”
Section: Methodsmentioning
confidence: 99%